Exploring the effort-reward structure of university work focusing on perceived overall stress, self-reported health, and musculoskeletal disorders - Bence Verpeléti; Edina Horváth; Gordana Dobi-Ágoston; Gergely Ágoston; Kitti Bérces; Regina Molnár; Veronika Mátó; Albert Varga; Edit Paulik (SAGE Publishing, 2021)
Background: The effort-reward imbalance (ERI) model by Siegrist encouraged numerous scientific investigations that reported particular ties between psychosocial risks and poor self-reported health (SRH), while psychosocial work-related stress has also been linked to musculoskeletal disorders (MSDs). The aim of this study was to examine the health status and the perceived levels of occupational stress of university employees and to analyse the findings according to the employees' effort and reward structure of work, perceived overall stress, SRH and the presence of MSDs.   Design and methods: 398 employees - including healthcare professionals, academic personnel and workers with administrative or other jobs - employed at the University of Szeged, Faculty of Medicine were investigated with a self-administered questionnaire including the Effort-Reward Imbalance Questionnaire (ERI-Q) and Perceived Stress Scale 4 (PSS-4). Results: More than half of the investigated subjects (54.8%) reported some forms of MSDs. Low self-reported health (p<0.001) and presence of MSDs (p=0.015) were significantly associated with the level of perceived stress and effort-reward imbalance (ERI), moreover increased level of perceived stress was independently associated with the likelihood of MSDs (AOR=1.13) and low self-reported health (AOR=1.30). ERI well predicted low self-reported health (AOR=2.05) as well. Increased level of perceived stress positively correlated with high work-related effort (r=0.247, p<0.001) and over-commitment (r=0.387, p<0.001) while with work-related reward (r=−0.181, p=0.011) perceived stress showed a negative connection. Conclusion: Our results suggest that addressing the burden of effort-reward imbalance and MSDs would likely lessen employees' perceived level of overall stress and affect their self-reported overall state of health.